Formulation, Physicochemical Characterization, and Antibacterial Activity of Ethanolic Rosa spp. Extract Topical Gel Against Cutibacterium acnes - Diki Zaelani; Abdul Mulki Irfani; Merylance Stefany Sanggo; Jajang Japar Sodik; Reza Pratama (Tropical Biopharmaca Research Center, IPB University, 2026)
his study evaluated a topical gel containing ethanolic red rose (Rosa spp.) extract against Cutibacterium acnes. Phytochemical screening identified alkaloids, flavonoids, tannins, and anthocyanins. Five gel formulas were developed using 0.25–1.25% Carbopol 940. All formulations showed pseudoplastic flow characteristics. Measured pH values ranged from 7.02 to 7.08, indicating a need for adjustment to meet physiological skin pH (4.5–5.5). Formulas with 0.5% and 0.75% Carbopol (F2 and F3) exhibited the most balanced viscosity, spreadability, and adhesiveness. In vitro antibacterialtests via disc diffusion showed inhibition zones of 14–15 mm against C. acnes. These results indicate that the extract can be formulated into a stable gel while maintaining antibacterial activity. Future optimization should focus on pH correction and long-term stability to ensure dermatological safety.